The Effect Ofjuice Red Guava and Juice Pineapple Consumption on Hemoglobin Levels in Postpartum Women in The Service Area Puskesmas Purwokerto Selatan - Intan Salsabila; Yektiningtyastuti Yektiningtyastuti; Happy Dwi Aprilina; Jumiati Riskiyani Dwi Nandia (Universitas Malahayati Lampung, 2026)
ABSTRACT Pregnancy involves the development of a fertilized fetus in the uterus for approximately 40 weeks, accompanied by various physiological changes in the mother's body. One such change is hemodilution, which can decrease hemoglobin levels. Low hemoglobin levels during pregnancy increase the risk of bleeding during delivery and can lead to postpartum anemia. This study investigated how consumption of guava juice and pineapple juice affects hemoglobin levels in postpartum mothers. This study used a pre-experimental design with a two-group pretest-posttest design on 45 postpartum mothers divided into two groups: one group consumed 250 mL of guava juice daily and the other group consumed 250 mL of pineapple juice daily for 7 days. Hemoglobin levels were measured before (pretest) and after (posttest) the intervention. Data analysis using an independent t-test comparing the two groups before the intervention (pretest) yielded a p-value of 2.680, and after the intervention (posttest) a p-value of 6.770, indicating no significant difference between the two groups in either the pretest or posttest. The results of a paired t-test comparing the pretest and posttest in each group showed that hemoglobin levels increased significantly after consuming guava juice (p = 0.000) and pineapple juice (p = 0.000). These findings suggest that consuming guava or pineapple juice for 7 days can effectively increase hemoglobin levels in postpartum mothers. Keywords: Hemoglobin, Guava Juice, Pineapple Juice, Postpartum. ABSTRAK Kehamilan melibatkan perkembangan janin yang telah dibuahi di dalam rahim selama sekitar 40 minggu, bersamaan dengan berbagai perubahan fisiologis dalam tubuh ibu. Salah satu perubahan tersebut adalah hemodilusi, yang dapat menurunkan kadar hemoglobin. Kadar hemoglobin rendah selama kehamilan meningkatkan risiko perdarahan saat persalinan dan dapat menyebabkan anemia pascapersalinan. Studi ini menyelidiki bagaimana konsumsi jus jambu merah dan jus nanas memengaruhi kadar hemoglobin pada ibu postpartum. Studi ini menggunakan desain pre-experimental, dengan rancangan two-group pretest-posttest pada 45 ibu postpartum yang dibagi menjadi dua kelompok: satu kelompok mengonsumsi 250 mL jus jambu merah setiap hari dan kelompok lainnya mengonsumsi 250 mL jus nanas setiap hari, selama 7 hari. Kadar hemoglobin diukur sebelum (pretest) dan setelah (posttest) intervensi. Analisis data menggunakan uji t-independent yang membandingkan kedua kelompok sebelum intervensi (pretest) menghasilkan nilai p sebesar 2,680 dan setelah intervensi (posttest) nilai p sebesar 6,770, yang menunjukkan tidak ada perbedaan signifikan baik pretest maupun posttest antara kedua kelompok. Hasil uji paired t-test yang membandingkan pretest dan posttest pada masing-masing kelompok menunjukkan bahwa kadar hemoglobin meningkat secara signifikan setelah mengonsumsi jus jambu merah (p = 0,000) dan jus nanas (p = 0,000). Temuan ini menunjukkan bahwa mengonsumsi jus jambu merah atau nanas selama 7 hari dapat secara efektif meningkatkan kadar hemoglobin pada ibu postpartum. Kata Kunci: Hemoglobin, Jus Jambu Biji Merah, Jus Nanas, Postpartum.